Non-radioisotopic glucose turnover in children with falciparum malaria and enteric fever - Balbir, Singh; Keng, E. Choo; Jamal, Ibrahim; Johnston, Wayne; Davis, Timothy M.E. (Elsevier Ltd., 1998)
To determine whether glucose turnover is increased in acute falciparum malaria compared to enteric fever in children, steady-state 6,6-D2-glucose turnover was measured in 9 Malaysian children with uncomplicated malaria (6 males and 3 females; median age 10 years, body weight 22 kg) and in 12 with uncomplicated enteric fever (8 males and 4 females; median age 10 years, body weight 24 kg) in acute illness, after quinine (5 malaria patients) and in convalescence. Baseline plasma glucose concentrations in malaria and enteric fever were similar (all values are medians [ranges in brackets]) 5·6 [3·2–11·3] vs. 5·5 [4·2–8·0] mmol/L), as were serum insulin levels (5·6 [0·4–26·5] vs. 6·8 [1·1–22·5] milliunits/L; P > 0·4). Glucose turnover in the malaria patients was higher than in patients with enteric fever (6·27 [2·71–6·87] vs. 5·20 [4·50–6·08] mg/kg.min; P = 0·02) and in convalescence (4·74 [3·35–6·79] mg/ kg.min; P = 0·05 vs. acute malaria study), and fell after quinine together with a rise in serum insulin (P = 0·03). Basal plasma lactate concentrations were higher in enteric fever than in malaria (3·4 [1· 8–6·4] vs. 0·8 [0·3–3·8] mmol/L; P < 0·0001) and correlated inversely with glucose turnover in this group (rs = −0·60; n = 12; P = 0·02).These data suggest that glucose turnover is 20% greater in malaria than in enteric fever. This might reflect increased non-insulin-mediated glucose uptake in falciparum malaria and/ or impaired gluconeogenesis in enteric fever, and may have implications for metabolic complications and their clinical management in both infections.